A Qualitative Study of Teachers’ Perceptions of Children’s Physical Activity and Learning in Preschool - Waode Eti Hardiyanti; Muhammad Ilham (Institut Agama Islam Negeri Kendari, 2019)
AbstractThe aimed of this research is to examine teachers’ perception of physical activity that can indicate the level of physical activities displayed in children’s classroom. Semi-formal interviews were conducted with six early childhood teachers. Results of the study indicated that early childhood teachers used physical activity to promote the learning materials. The teachers stated that through their physical activities, children might develop a better comprehension of academic concepts. The teachers also reported that children’s positive attitudes improved when physical activity was undertaken, particularly evidenced by an increase in children’s confidence and enthusiasm during the learning process. However, inadequate opportunity to include physical activity in preschool due to limited equipment, deterred teachers from truly facilitating the physical activities of children. The teachers were also concerned that their ability and understanding to accommodate physical activity may not be adequate for the children. Therefore, underpinning the teacher’s role with training may be required in order to cover the children’s needs to actively engage in physical activities as mentioned in curriculum.